(3ahGFO CHj GdbGSe GdeDed Hf CMeO Hf eMeO GdTjHGfis - (3Nda GdMGaX GdhGSWjs
(3ChdgG (B:s
(3CNHQfG GdTjN GdCejf CHh GdecGQe YHO GdhGMO Hf eMeO Hf Sede Hf gdGd bOeJ (B: (3jG QShd Gddg CeG Jchf GdPcGI EdG ef GdMdb Ce GddHI ? bGd (B: (3dh WYfJ ai aNPgG dCLRGc s
(3BNQgG (B:s
(3Yf GdTYHi bGd (B: (3eG CMOi (B( (3? (B) (3eG Jbhdhf , EPG cGf cPGHG agh efGab BNQg hGdMeO ddg s
(3HBNQgG SeGYGJ HYVgG SfI (B590 (3hHYVgG SfI (B656 (3hGdSeGY Ydi GdMGaX CHj eMeO YHO GdZfi Hf YHO GdhGMO Hf SQhQ GdebOSi hCMeO YHO GdOGFe GdebOSi hcJH gPG HNWg dUMI GdSeGYs
(3HGdfSNI ChQGb HNW eZGjQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3eLGejY (B124) s
Keywords: (3GdMOjK h GdeUWdMs